Implementasi Peraturan Gubernur DKI Jakarta Nomor 77 Tahun 2020 tentang Pengelolaan Sampah Dalam Meningkatkan Kualitas Lingkungan di RW 015 Kelurahan Duren Sawit, Kota Administrasi Jakarta Timur. - Fitri Heri Kustanti; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Discussing public awareness of the environment they live in recently can be said to be worrying, but this situation does not occur in the RW.015 Duren Sawit Village environment. This is an interesting topic to discuss, how this could happen, while there are some people who no longer believe that there are villages where the community still plays an active role. What factors exist to create an environment that they call "BERSINAR" (Clean, Healthy, Beautiful, Comfortable, Neat). This research uses normative and empirical methods by collecting interview data, namely to find factors that create a "BERSINAR" environment. The results of this research show that in creating a "BERSINAR" environment, sub-district officials and their staff must play an active role and work in synergy so that high public awareness is created, so there is nothing difficult and it is impossible for a "BERSINAR" environment to be realized.